Library Services During COVID 19: A Usability Analysis of Websites of the Central University Libraries in India - Verma, Nitesh Kumar; Deori, Maya; Verma, Manoj Kumar (DESIDOC Journal of Library & Information Technology, 2023)
Academic library websites are considered an integral tool for disseminating libraries’ information, resources, and services. It also encourages users to interact and use library resources and services remotely. The spread of COVID-19 and the nationwide lockdown shifted the education system to an online mode of teaching and learning. The present study aims to analyse the usability criteria of the Central Universities’ library websites, the availability of various facilities & services provided during the pandemic, to know the mode of information dissemination during the pandemic, andthe preventive measures undertaken by the Central University library websites to combat the Corona Virus.The study reveals that Aligarh Muslim University and the Central University of Orissa have adopted all possible means and modes to provide information to its users to combat the struggles during the pandemic through their library websites. However, certain Central University websites like the Central University of South Bihar have provided the least services for their users during the pandemic. The study also highlighted the essential steps initiated by the selected libraries to fulfill the information needs of their users, and those services may be opted by others to meet the post-lockdown needs.